Personal meanings in the issues of life safety of humanitarian students - Pаntiouk, Irina V. (University Pedagogical Journal, 2023)
The psychological and pedagogical research on the problems of the meaning and meaning of transmission in the educational space, the translation of the message in the training on the formation of the personality of safe behaviour is analysed. The experience of using pedagogical semantic tasks and diagnostic cases in the study of the discipline «Human life safety» is summarised. Examples of problem solving of humanitarian students on issues of personal life safety are presented.
Keywords: personality; life safety; education; meaning; translation; safe behaviour